Zasada primogenitury równorzędnej i jej wdrażanie na podstawie wybranych państw europejskich .......... 111 - Jankowska, Julia (Współczesne zmiany konstytucji w wybranych państwach europejskich: Pomiędzy partykularyzmem prawnym a wspólnotą doświadczeń, 2025)
ABSOLUTE PRIMOGENITURE AND ITS IMPLEMENTATION BASED ON EXAMPLES OF CHOSEN EUROPEAN COUNTRIESToday European democracies have shifted their attention towards human rights. A lot of discussions carried out oscillate around them and many acts of law are issued to protect them. This movement can also be noticed in the remaining monarchies. Although there seems to be no problem in implementing changes regarding society as a whole, problem occurs when attention is switched towards certain rules that continue in monarchies. This can be noticed especially through analyzing the law of equality, or actually the lack of it in regards to females in the inner workings of royal families and the succession of the throne. A movement of changing this problem took place in similar time (2009-2011) for three European monarchies which changed their primogeniture to absolute primogeniture: the United Kingdom of Great Britain and Northern Ireland, the Kingdom of Denmark, and the Grand Duchy of Luxembourg. The purpose of this article is to answer whether these changes in the abovementioned countries were in any way caused by similar events or situations and could be connected, as well as wether implementing them was followed by the introduction of laws which were meant to protect women’s rights. Explanation of these points will be carried out based on an analysis of events and political situation in each country, as well as observation of the number of acts of law regarding women’s rights given out before and after the change to absolute primogeniture.